Characterizing forearm muscle activity in young adults during dynamic wrist flexion–extension movement using a wrist robot. (17th July 2020) - Forman, Davis A.; Forman, Garrick N.; Avila-Mireles, Edwin J.; Mugnosso, Maddalena; Zenzeri, Jacopo; Murphy, Bernadette; Holmes, Michael W.R.
Abstract: Current research suggests that the wrist extensor muscles function as the primary stabilizers of the wrist-joint complex. However, most investigations have utilized isometric study designs, with little consideration for wrist dynamics or changes in posture. The purpose of the present study was to assess forearm muscle activity during the execution of dynamic wrist flexion/extension in multiple forearm orientations (pronation/supination). In 12 young adult males, surface electromyography (EMG) was recorded from eight muscles of the dominant arm: flexor carpi radialis (FCR), flexor carpi ulnaris (FCU), flexor digitorum superficialis (FDS), extensor carpi radialis (ECR), extensor carpi ulnaris (ECU), extensor digitorum (ED), biceps brachii (BB) and triceps brachii (TB). While grasping a handle, participants performed dynamic wrist flexion/extension using a three-degrees-of-freedom wrist manipulandum. The robotic device applied torque to the handle, in either a flexion or extension direction, and in one of three forearm postures (30° supinated/neutral/30° pronated). Results indicated that forearm posture had minimal influence on forearm muscle activity, but significantly altered the activity of the biceps and triceps brachii. Movement phase (concentric-eccentric) dictated muscle activity in every muscle. Interestingly, muscle activity in the eccentric phase was equal between the two applied handle torques, regardless of whether the muscle acted as the agonist or antagonist. Co-contraction ratios were higher in the flexion conditions (flexion: 2.28 ± 2.04, extension: 0.32 ± 0.27), suggesting significantly greater wrist extensor activity–likely a contribution to wrist joint stability. This highlights the vulnerability of the wrist extensor muscles to overuse injuries in settings requiring prolonged use of dynamic wrist exertions.